(untitled) (International Journal of Scientific Research in Science and Technology, 2025)
Plumeria alba, popularly known as white frangipani, is a little decorative tree that is well known for its cultural, medicinal, and aesthetic values. This review emphasises current scientific knowledge on the botanical description, phytochemistry, pharmacological properties and potential applications of P. alba. Studies indicate that the plant possesses various bioactive compounds with therapeutic potentials, including antimicrobial, antiarthritic and antioxidant effects. However, further clinical research is warranted to validate these findings and explore sustainable uses of this species.